(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we examine the properties of completeness and compactness on hesitant fuuzy normed linear space, also address the same properties on intuitionistic hesitant fuuzy normed linear space in finite dimension using definitions, lemmas, and theorems. We also investigate the continuity of underlying t-norms and co-t-norm on finite-dimensional intuitionistic hesitant fuzzy normed linear space.